Variation in the belly barrings of the Greenland White-fronted Goose Anser albifrons flavirostris - Kristiansen, J N; Walsh, A J; Fox, A D; Boyd, H; Stroud, D A (Wildfowl, 1999)
Based on data from seven successive years from the wintering grounds in Ireland and one year from the breeding grounds in West Greenland, the variation in the black striation on the abdomen and breast, the so-called belly barring, of the Greenland White-fronted Geese Anser albifrons flavirostis was assessed. We analysed for sexual variation, age variation, year to year variation and seasonal variation [early winter (1 October - 31 December) and late winter (1 January - 31 April)]. Geese showed no sexual difference, no change with age after the first winter and no clear pattern in year to year variation. However, there was a highly significant seasonal variation, since individual birds became consistently darker in late winter.